2017
DOI: 10.1016/j.aquaculture.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tilapia Lake Virus in Egypt in Nile tilapia affected by ‘summer mortality’ syndrome

Abstract: M (2017) Identification of Tilapia Lake Virus in Egypt in Nile tilapia affected by 'summer mortality' syndrome, Aquaculture, 473, pp. 430-432.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
125
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 3 publications
7
125
1
3
Order By: Relevance
“…Up-to-date, TiLV has been publicly reported in Israel, Ecuador, Colombia, and Egypt (Eyngor et al, 2014;Ferguson et al, 2014;Tsofack et al, 2016;Fathi et al, 2017). This study has confirmed the presence of TiLV associated with high mortalities (20-90%) in tilapia farms in Thailand, one of the major tilapia producers in Asia.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Up-to-date, TiLV has been publicly reported in Israel, Ecuador, Colombia, and Egypt (Eyngor et al, 2014;Ferguson et al, 2014;Tsofack et al, 2016;Fathi et al, 2017). This study has confirmed the presence of TiLV associated with high mortalities (20-90%) in tilapia farms in Thailand, one of the major tilapia producers in Asia.…”
Section: Discussionsupporting
confidence: 90%
“…Niloticus in Egyptian farms (Fathi et al, 2017). This study also found natural infections of TiLV in fingerlings of red and Nile tilapia reared in both earthen pond and open cage system in three different provinces in Thailand.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Both multivariate models show that excess mortality of tilapia due to the SHT increased when stocking density was increased. A previous study reported that stocking density of tilapia contributed to the presence of TiLV (Fathi et al., ). It has been reported that stocking density is inversely proportional to the total body weight, daily weight gain and length of Nile tilapia fingerlings which impacts on the immunity of the fish (Breine, Nguenga, Teugels, & Ollevier, ; Sanudi, Jere, Mzengereza, & Chirwa, ).…”
Section: Discussionmentioning
confidence: 98%
“…Several outbreaks of TiLV with mortalities reaching 90% have been reported in Thailand (Dong et al., ). In Egypt, the disease has been reported to cause summer mortalities (5%–15%) in numerous farms (Fathi et al., ). The identity of the associated virus in all of these distinct pathological presentations was shown to be an RNA virus (Eyngor et al., ; Tsofack et al., )‐related genetically (Bacharach et al., ) and morphologically to the Orthomyxoviridae family (del‐Pozo et al., ).…”
Section: Introductionmentioning
confidence: 99%